Indoor Localization berbasis RSS Fingerprint Menggunakan IEEE 802.11n - Widyawan, Widyawan (2012)
This paper discuss about indoor localization using IEEE 802.11n wireless network using RRS- based fingerprint technique. To perform indoor localization, Nearest Neighbor (NN) algorithm is employed. This research is conducted in hallways at 3rd floor of EE and IT Department building, Gadjah Mada University with total dimension of 1969.68 m2. Fingerprint map is built with two different resolutions (i.e 1m2 and 2m2). Evaluation of the localization technique is performed under four configurations. The result show that the smaller grid dimension is, the closest the estimated distance is (error is reduced to 2.386 meter). The number of wireless access points that used in fingerprinting also affects the localization performance, adding more access points reduce the localization error to 4.1311 meter.